2018
DOI: 10.1080/13697137.2018.1458833
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian aging: an ongoing prospective community-based cohort study in middle-aged Chinese women

Abstract: This is the first population-based prospective cohort study exploring the ovarian aging process in Chinese women. A large sample size and long follow-up duration were achieved. Detailed analysis of data obtained from this cohort will be provided in future reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Finally, there were some differences in BMI, marital status, education, and general health status between the premenopausal women and postmenopausal women at baseline, mainly due to increasing ages. The postmenopausal women at baseline had an earlier menopausal age because they recalled their menopausal age, which could be approximately 1 to 2 years earlier than the real menopausal age, as has been shown by other studies (17,25). However, a repeat analysis excluding women who were postmenopausal at baseline found that the results were not altered, suggesting that any inaccuracies in women's recollection of their menopausal age did not bias the results.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Finally, there were some differences in BMI, marital status, education, and general health status between the premenopausal women and postmenopausal women at baseline, mainly due to increasing ages. The postmenopausal women at baseline had an earlier menopausal age because they recalled their menopausal age, which could be approximately 1 to 2 years earlier than the real menopausal age, as has been shown by other studies (17,25). However, a repeat analysis excluding women who were postmenopausal at baseline found that the results were not altered, suggesting that any inaccuracies in women's recollection of their menopausal age did not bias the results.…”
Section: Discussionsupporting
confidence: 64%
“…An exchangeable working correlation matrix that accounts for correlations within subjects was used. Because women who were postmenopausal at enrollment (n ¼ 190) may not have recalled their age at menopause accurately due to recall bias (17,25), we repeated the analysis with these women excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The control group included 111 post-menopausal women. The comparison data is from the PUMCH Aging Longitudinal Cohort of Midlife Women (PALM), a prospective, open-cohort, which involved with a community-based longitudinal study, aiming to investigate ovarian ageing in midlife women in China [ 29 ]. The participants were middle-aged female residents of the TieEr community, Xicheng District, Beijing, China.…”
Section: Methodsmentioning
confidence: 99%